Lipomas are associated with a higher prevalence of metabolic syndrome components: a multicenter cross-sectional study - Berger, Ori; Menashe, Shaked; Damti Geva, Shiri; Yakubov, Reychel; Ben Yehuda, Maor; Peleg, Mor; Talisman, Ran (Frontiers in Endocrinology, 2025)
IntroductionLipomas are the most common benign adipocytic tumors and are traditionally regarded as incidental findings with cosmetic significance. However, their frequent occurrence in adults with obesity and metabolic risk factors raises the possibility that lipomas may reflect systemic metabolic dysfunction rather than isolated adipose overgrowth. The present study evaluated whether adults with lipomas have a higher prevalence of metabolic syndrome components, obesity, dyslipidemia, hypertension, and type 2 diabetes mellitus (T2DM), compared with population benchmarks.MethodsWe conducted a retrospective, multicenter, cross-sectional analysis of electronic health records from three Israeli hospitals (Barzilai, Shamir, and Galil Medical Centers) between January 2000 and December 2022. Adults aged ≥21 years with a clinical diagnosis of lipoma (ICD-9-CM 214) were included. Data were harmonized using the Observational Medical Outcomes Partnership (OMOP) Common Data Model and analyzed via the Lynx real-world health data platform. Prevalence of obesity, dyslipidemia, hypertension, and T2DM was compared against age- and sex-specific benchmarks from the 2023 Israeli Knowledge, Attitudes, and Practices (KAP) survey. Subgroup comparisons used Z-tests or exact binomial tests with α = 0.05, reporting absolute differences with 95% confidence intervals.ResultsA total of 7,868 adults with lipomas were analyzed (mean [SD] age, 53.0 [15.0] years; 53.6% women). Compared with population benchmarks, lipoma patients showed consistently higher prevalence of all four metabolic traits. Dyslipidemia was most overrepresented, followed by hypertension and obesity, while T2DM showed a uniform excess across all age and sex subgroups. Clustering of three or more metabolic traits—consistent with metabolic syndrome, was common after age 35 and most pronounced in midlife.ConclusionAdults with lipomas exhibit a substantially higher burden of metabolic syndrome components compared with population norms. These findings suggest that lipomas may serve as visible clinical indicators of systemic metabolic dysfunction. Recognizing lipomas as potential cutaneous markers of cardiometabolic risk could improve early identification of individuals at risk for obesity-related and endocrine diseases and support integration of dermatologic and metabolic screening practices.